Evaluating The Financial Performance And Its Role In Rationalizing Investment Decisions In The Commercial Bank Of Tartous - منصور يُمن; ابراهيم نغم (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research aims to identify the reality of the financial performance of the branches of the Commercial Bank in Tartous and to show its impact on rationalizing investment decisions. To achieve this, a questionnaire was distributed to a sample of 128/ of workers in the branches of the Commercial Bank in Tartous, and the research relied on the descriptive analytical method. The research reached the following results: - The financial performance of the branches of the Commercial Bank in Tartous is strong, and the bank is interested in modernizing its financial system and constantly qualifying its employees to keep pace with developments and technology. - Evaluating the financial performance affects the rationalization of the investment decision in the branches of the Commercial Bank in the city of Tartous, where the results of the applied tests showed a positive relationship between them, meaning that working towards developing the financial performance in Egypt is positively reflected in its ability to rationalize the investment decision. -The ability variable (confronting emergency changes) is considered the most variable capable of influencing the rationalization of the investment decision, followed by the variable (qualifications and experiences of employees) and finally (electronic modernization and development).